Peningkatan Kesadaran Masyarakat terhadap Pengendalian Risiko Kardiovaskular dengan Skrining Kolesterol Total dan HDL di Yayasan Baptis Cengkareng - Martin, Alfianto; Santoso, Alexander Halim; Destra, Edwin; Alexandro, Cristian; Edbert, Juan; Anthony, Louis (jurnal ABDIMAS Indonesia, 2025)
Total cholesterol and HDL assessments are fundamental initial steps in evaluating the risk of cardiovascular disease. The ratio between total cholesterol and HDL is considered a sensitive indicator in predicting atherosclerotic events. Screening activities were carried out using the Plan-Do-Check-Act (PDCA) approach in adult participants. The examination was carried out using the Point-of-Care Testing (POCT) tool to assess total cholesterol and HDL levels from blood samples. Education was provided through leaflets containing information about lipid profiles and the importance of dietary changes. A total of 62 participants took part in this activity, with an age range of 23 to 76 years and the majority were female. Most participants had total cholesterol levels in the normal category, but almost all participants had HDL levels that were classified as low or very low. This lipid profile imbalance indicates a significant potential cardiovascular risk. The screening results underscore the need for continuous education on healthy dietary habits as a primary prevention strategy. Nutritional interventions emphasizing reduced intake of saturated fats, increased fiber consumption, and controlled sugar intake can help restore lipid balance and reduce the risk of atherosclerosis and long-term cardiovascular complications.